Mejora de la calidad de semillas de Gatton Panic mediante el empleo de plasma no-térmico - Pérez Pizá, María Cecilia; Clausen, Liliana; Cejas, Ezequiel; Ferreyra, Matías Germán; Zilli, Carla Giannina; Vallecorsa, Pablo Daniel; Prevosto, Leandro; Balestrasse, Karina Beatriz (Asociación de Laboratorios Agropecuarios Privados (ALAP); Facultad de Ciencias Agropecuarias de la Universidad Nacional de Córdoba, 2022)
Póster y resumen